STRUKTUR INDUSTRI TAS KAMERA UNTUK MENENTUKAN STRATEGI BERSAING DI INDONESIA - David Sukardi Kodrat (Universitas Bunda Mulia, 2016)
This study aims to investigate the relative strength of camera case industries in Indonesia and measures how much their relative strength influences on their competitive strategy. There is five industries structure which involved in this study, namely competitors (13 companies), new entrants, customers, subtitutes of product (2 companies), and main suppliers which supplies raw materials. Sampling techique was cluster in term of type of industries such as competitrors, new entrants customers, subtitutes of product, and suppliers. Competitive strategy is as dependent variable (Y) and bargaining from supplier (X1), customers (X2), threat from new entrants (X3) subtitutes of product (X4) and rivalry among industries (X5) are as independent variables. The indicators for those variables was adopted from Cunningham (2012), Alrawasdeh (2013), dan Kodrat (2009). And analyzed through multiple regression analysis. The result shows all of the independent variables was simultaneosly affect to competitive strategy significantly.Keywords: camera cases industry, supplier, customers, subtitute products, competitors, new entrants.